Contexts of W. Golding's Novel "Lord of the Flies" - Válek, Lukáš (Univerzita Pardubice, 2014)
The main focus of the paper is to describe and analyze the contextual aspects of William Golding's Lord of the Flies and compare them to R. M. Ballantyne's The Coral Island. The paper begins with an introduction to the lives of both authors and their works. Then in the following part the paper describes the nineteenth and the twentieth century correlating to both novels. It then analyzes and compares the characters and motifs of both books, with a relation to the historical contexts.
Kontexty Goldingova románu "Pán much"
Keywords: Golding, William; Lord of the Flies; Ballantyne, R. M.; Coral Island; Pán Much; Korálový Ostrov